Geglaubte Verzweiflung Wider eine atheistische Lesart Kierkegaards und ihre Ursächlichkeits-Rhetorik - Junker, Tobias (2016)
In Kierkegaard’s The Sickness unto Death the self’s other is usually identified with God. But because the sickness of the title is despair, the religious dimension of this text should be considered with particular regard to its psychological dimension. Indeed, one might ask, if meaningful talk about the self is, according to Anti-Climacus, grounded in (Christian) faith or if the latter’s actual usage of the term “despair” much rather implies that the self’s origin and nature can be fully captured from a non-theistic and in fact purely scientific perspective, a perspective which in turn is bound up with or at least gravitates toward existentialism. As I will argue, this second interpretation, which has most recently been defended by Rasmus Rosenberg Larsen, misses crucial points in Kierkegaard’s (mis‐)usage of causality and thus cannot be sustained.